Investigations on small molecule inhibitors targeting the histone H3K4 tri-methyllysine binding PHD-finger of JmjC histone demethylases. Issue 11 (15th July 2018) - Bhushan, Bhaskar; Erdmann, Alexandre; Zhang, Yijia; Belle, Roman; Johannson, Catrine; Oppermann, Udo; Hopkinson, Richard J.; Schofield, Christopher J.; Kawamura, Akane
Graphical abstract: Abstract: Plant homeodomain (PHD) containing proteins are important epigenetic regulators and are of interest as potential drug targets. Inspired by the amiodarone derivatives reported to inhibit the PHD finger 3 of KDM5A (KDM5A(PHD3)), a set of compounds were synthesised. Amiodarone and its derivatives were observed to weakly disrupt the interactions of a histone H3K4me3 peptide with KDM5A(PHD3). Selected amiodarone derivatives inhibited catalysis of KDM5A, but in a PHD-finger independent manner. Amiodarone derivatives also bind to H3K4me3-binding PHD-fingers from the KDM7 subfamily. Further work is required to develop potent and selective PHD finger inhibitors.